Validation of IgG-sandwich and IgM-capture ELISA for the detection of antibody to Rift Valley fever virus in humans - Paweska, Janusz T.; Burt, Felicity J.; Swanepoel, Robert (Journal of virological methods, 2005)
Rift Valley fever (RVF) virus is an important zoonotic and a potential biothreat agent. This paper describes validation of sandwich and capture enzyme-linked immunoassays (ELISA) based on gamma-irradiated antigens for the detection of RVFV-specific IgG and IgM antibody in humans. Validation data sets derived from testing field-collected sera from Africa ( n = 2400) were dichotomised according to the results of a virus neutralisation test. In addition, sera from laboratory workers immunized with inactivated RVF vaccine ( n = 93) and serial sera ( n = 3) from a single RVF case were used. ELISA data were expressed as percentage of high-positive control serum (PP). Cut-off values at 95% accuracy level were optimised using the misclassification cost term option of the two-graph receiver operating characteristics analysis. During the routine use of assays there was no evidence for excessive intra- and inter-plate variations within and between runs of assays. At a cut-off of 13.2 PP the sensitivity of the IgG-sandwich ELISA was 100% and specificity 99.95%, while for the IgM-capture ELISA the values were 96.47 and 99.44%, respectively, at a cut-off of 7.1 PP. Compared to the virus neutralisation test, the IgG-sandwich ELISA was more sensitive in detection of immunological responses in vaccines. Following natural infection class-specific antibodies were detected in serum taken 6 days after onset of symptoms. The results demonstrate that both assays will be useful for early diagnosis of infection, epidemiological surveillance and for monitoring of immune response after vaccination. As highly accurate, robust and safe tests, they have the potential to replace traditional diagnostic methods which are unable to distinguish between different classes of immunoglobulins, and pose health risks necessitating their use being restricted to high containment facilities outside RVF endemic areas.